PENGARUH RASIO KEUANGAN TERHADAP HARGA SAHAM: KEBIJAKAN DEVIDEN SEBAGAI VARIABEL INTERVENING - Hardiansyah, Septian Novan (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to analyze and to test the influence of financial performance which is measured by using financial ratio measuring instrument on manufacturing companies which are listed in Indonesia Stock Exchange. Some variables which are used in this research are: financial ratio, dividend policy, and share price. Based on the result of overall hypothesis test it can be concluded that dividend policy (DPR) can be an intervening variable between share price and independent variables which consist of return on asset (ROA), return on equity (ROE), debt equity ratio (DER) and current ratio (CR) variables, and dividend policy (DPR) cannot be an intervening variable between share price and independent variables: gross profit margin (GPM), net profit margin (NPM) and total asset turn over (TATO).Keywords: Financial Ratio, Dividend Policy, and Share Price.